Analisis Manajemen Risiko Di Ruang Filing RSUD dr Soediran Mangun Sumarso Wonogiri Tahun 2020 - Nabilatul Fanny; Anindiya Soviani (Universitas Duta Bangsa Surakarta, 2020)
Patient safety is a system that makes patient care safer, including risk assessment, identificationand management of patient risks, incident reporting and analysis, the ability to learn from incidents andtheir follow-up, and implementation of solutions to minimize risks and prevent injury caused by errors.the result of carrying out an action or not taking the action that should be taken The importance of riskmanagement in the hospital is to minimize the number of unwanted events. Based on a preliminary studyof five medical record processing at the Dr Soediran Mangun Sumarso Wonogiri Regional Hospital, thebigger risk is filing, in the medical record unit there is no standard risk management operationalprocedure and there is no report related to risk management. This type of research is descriptive with across sectional approach. The subjects are the Facility Management and Safety coordinator, head ofmedical records, and head of filing. The object of the filing room and the risk management process. Theresearch instruments were observation guidelines and interview guidelines. Data analysis was carriedout by univariate. The results show that risk management at Dr Soediran Mangun Soemarso WonogiriHospital has been carried out. Safety Facility Management is a working group to plan risk managementin each unit. The medical record unit of Dr Soediran Mangun Soemarso Wonogiri Hospital implementsrisk management with an appropriate sequence of risk management processes starting fromcommunication consultation, scope of context criteria, risk assessment, risk treatment, monitoring andreview. In the filing section of the Dr Soediran Mangun Soemarso Wonogiri Regional Hospital, there isone important stage that is overlooked in the risk management process, namely the scope, context, andcriteria stages. The conclusion of this study is that the Facility and Safety Management section hasimplemented a risk management process in the medical record unit but has not been maximallyimplemented in the filing section.